Stress-strain behavior of saturated clay and basic strength principles / by Charles C. Ladd. - Ladd, Charles C. (Charles Cushing); Massachusetts Institute of Technology. Soil Mechanics Division.; United States. Army Materiel Command.; United States. Advanced Research Projects Agency.; U.S. Army Engineer Waterways Experiment Station. (Tufts University. Tisch Library., 2019)
1 online resource : illustrations.; "Cosponsored Army Materiel Command Project Nos. 1-A-0-1101-B-021-30 and 1-T-0-21701-A-046-05 and Advanced Research Projects Agency ARPA Order no. 400 Contract No. DA-22-079-eng-330 with U.S. Army Engineer Waterways Experiment Station."; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.